Impact of winch-assisted logging machinery on soil disturbance in the mountainous forests of Western Carpathians - Allman, Michal; Dudáková, Zuzana; Duchan, Martin; Jankovský, Martin; Juško, Vladimír (Frontiers in Forests and Global Change, 2024)
Introduction Timber harvesting on steep terrain is a challenge in terms of economic viability, safety, and environmental performance. Felling with chainsaws and use of yarders seems optimal in this environment. However, using mobile traction winches allows for the safe work of ground-based technologies even in these challenging conditions. Methods Our study assessed the impact of winch-assisted cut-to-length harvesting on soil disturbance in young forest stands (up to 40 years old) across slopes of 14.9°-27.4° (27–52%). Utilizing 78 measurement points (i.e., 234 measurements), we analyzed soil samples from trail ruts, between ruts, and undisturbed areas for soil bulk density (g.cm−3) and soil moisture content (%), simultaneously measuring penetration resistance (MPa), penetration depth (cm) and rut depth (cm). Results The results highlighted that areas without winch assistance experienced the most significant increases in soil bulk density (up to 22.35%) and penetration resistance (up to 26.8%), though these differences were not statistically significant. Linear mixed effects models did not confirm a significant effect (p > 0.05) of a traction winch on the soil bulk density (g cm−3) and penetration resistance (MPa) in the ruts of the forwarding trails. Mean forwarding trail profile depths ranged from 4.63 to 7.28 cm, with the maximum depths between 10.86 and 17.25 cm, showing deeper ruts in non-assisted areas. Moreover, the presence of the traction winch (p < 0.05) significantly affected the maximal depth of the forwarding trail rut. Conclusion The findings suggest that winch-assisted harvesting may mitigate soil disturbance (rut depths) on steep slopes, offering a sustainable option for utilizing ground-based machinery with reduced environmental impact.